Business formation: A tale of two recessions - Ermin Dinlersoz; Timothy Dunne; John C. Haltiwanger; Veronika Penciakova (Federal Reserve Bank of Atlanta, 2021)
The trajectory of new business applications and transitions to employer businesses differ markedly during the Great Recession and the COVID-19 recession. Both applications and transitions to employer startups decreased slowly but persistently in the post-Lehman crisis period of the Great Recession. In contrast, during the COVID-19 recession new applications initially declined but have since sharply rebounded, resulting in a surge in applications during 2020. Projected transitions to employer businesses also rise, but this projection is dampened by a change in the composition of applications in 2020 toward applications that are more likely to be nonemployers.
Keywords: D2; E65; G33; 330; COVID-19; business failures; liquidity; small business